Exploring Resilience and Mental Health Among Canadian Inuit Youth: Understanding Wellness and Piloting a Prevention Program - Litwin, Leah Hart (2020)
Canadian Inuit youth in Nunavut struggle with higher rates of depression and suicide in comparison to youth in other parts of the world, yet accessible mental health services are lacking in the territory. The current project was comprised of three studies. Study 1 examined the accessibility and effectiveness of an e-intervention program, SPARX. SPARX was developed in New Zealand in collaboration with Mori communities, with the goal of supporting Mori Indigenous youth in decreasing symptoms of depression and boosting resilience. A modified randomized control trial was used to evaluate the effectiveness of SPARX in Nunavut with 49 Canadian Inuit youth across 11 communities. Outcome measures assessing: 1) symptoms of depression; 2) symptoms of hopelessness; 3) cognitive emotion regulation strategies; and 4) resilience were assessed. T-test and Anova statistics suggested that participating Canadian Inuit youth experienced less hopelessness and enhanced cognitive emotion regulation strategies after engaging in SPARX. No statistical changes in depression or resilience were noted. Study 2 used focus groups to gain a qualitative understanding of Canadian Inuit youths experience with SPARX. Youth from Study 1 participated in the Study 2 focus groups. Focus groups were recorded and transcribed, and coded using inductive thematic analysis. Results suggested that youth found the intervention engaging and interactive, and though it aligned well with youth culture, there was a reported desire for a more culturally appropriate version of SPARX. Study 3 used focus groups, across four communities in Nunavut, to delve deeper into the understanding of mental health and mental illness among Canadian Inuit youth. Youth and Elders in four communities were recruited to participate in these focus groups. Focus groups were recorded and transcribed, and coded using inductive thematic analysis. By engaging Elders in conversations about Canadian Inuit history, traditions and current barriers to accessing mental health programs, youth were ...